Method for improving plasticity of amorphous alloy
Through the medium-frequency induction smelting technology of high-purity graphite crucible, small atom C diffused to the amorphous alloy gap, solving the problem of limited macroscopic plasticity of amorphous alloys, and achieving the effect of improving strong plasticity and reducing costs.
Patent Information
- Application Number
- CN202510069470.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2045-01-16
AI Technical Summary
The existing amorphous alloys have limited macroscopic plasticity during deformation, which can easily lead to catastrophic brittle breakage. The existing methods to improve plasticity are costly and complex, which limit their engineering applications.
High-purity graphite crucibles are equipped with medium-frequency induction smelting technology, which forces small atoms C in the high-purity graphite crucible to diffuse into the amorphous alloy gap, thereby increasing the free volume and amorphous degree of shear band.
It effectively improves the strong plasticity of amorphous alloys, has stable method technology, low cost and low energy consumption, and is suitable for alloys with different components and metal proportions.
Smart Images

Figure CN119859766A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of amorphous alloy preparation, and in particular to a method for improving the strength and plasticity of amorphous alloys. Background Art
[0002] Bulk amorphous alloys have the characteristics of both metals and glasses, and have unique physical, mechanical and chemical properties, such as high strength, high hardness and strong corrosion resistance, etc., and have considerable development potential in the field of engineering structural parts. However, one of the biggest obstacles restricting its practical application and promotion is that it usually exhibits limited macroscopic plasticity during deformation, and is usually less than 1%, which can easily cause catastrophic brittle fracture. The existing method to improve the macroscopic plasticity of amorphous alloys is to introduce trace heterogeneous elements into the amorphous body to improve the plasticity of the amorphous alloy, such as the alloying method of adding metal elements to the melt before casting, the method of introducing particles or fibers as the second phase, or the mechanical alloying method of element powder. Among all the methods, the most commonly used is to introduce carbide ceramic particles or small-sized atoms into the amorphous body to adjust the macroscopic plasticity of the amorphous alloy. However, although this method helps to improve the plasticity of amorphous alloys, this preparation method has the characteristics of high cost of ceramic particles, precise material ratio, and uncontrollable element melting loss, which seriously limits its engineering application. Therefore, there is an urgent need to seek a low-cost, technically stable forming method to effectively improve the strength and plasticity of amorphous alloys. Summary of the invention
[0003] In view of this, the present invention provides a method for improving the strength and plasticity of amorphous alloys, which adopts a high-purity graphite crucible equipped with medium-frequency induction melting technology to prepare amorphous alloys. During the melting process, small atoms C in the high-purity graphite crucible can be forced to diffuse into the gaps in the amorphous alloy, thereby increasing the free volume of the shear band and improving the degree of amorphism.
[0004] The technical solution adopted by the present invention to solve the above technical problems is:
[0005] A method for improving the strength and plasticity of an amorphous alloy, the improvement process is shown in the following steps:
[0006] S1, weighing each metal raw material according to the target atomic percentage, uniformly mixing and obtaining an alloy sample, dividing the alloy sample into multiple portions, and the multiple alloy samples are further divided into M groups, and the M groups of alloy samples are respectively placed in a medium frequency induction furnace equipped with a high-purity graphite crucible, and before induction melting of each alloy sample, the high-purity graphite crucible is first evacuated and filled with high-purity argon gas; at the beginning of melting, a different melting temperature is set for each group of alloy samples, and different melting times are set for different alloy samples in each group, and the time when the alloy sample is cleared is recorded as the timing zero point; after the melting of each alloy sample is completed, the molten alloys at different melting temperatures and melting times are respectively poured into a cooling mold for cooling, and a plurality of amorphous alloy samples diffused with C elements are obtained in sequence;
[0007] S2, obtaining the C content C(t) of each amorphous alloy sample in S1;
[0008] S3, determine the volume V of any alloy sample in S1, and deduce the contact area S between the alloy sample and the inner surface of the high-purity graphite crucible;
[0009] S4, obtaining the maximum C solubility Cs of the interface reaction of the alloy sample at the above different melting temperatures;
[0010] S5, based on the C content C(t) and the maximum C solubility Cs of each amorphous alloy sample, the rate constant k at different melting temperatures is obtained:
[0011]
[0012] Where Co is the initial C solubility of the alloy sample, and t is the melting time;
[0013] S6. Based on the rate constant k obtained in S5, the C increment of the alloy sample melted in a high-purity graphite crucible at any time can be obtained.
[0014] Furthermore, the pressure of the high-purity argon gas filled in the high-purity graphite crucible in S1 is 0.4 MPa to 0.6 MPa.
[0015] Furthermore, the high-purity graphite crucible in S1 is provided with a boron nitride ceramic sleeve on the outside to protect the sensor.
[0016] Furthermore, the cooling mold in S1 is a high-purity copper mold.
[0017] Furthermore, in S2, the C content C(t) of each amorphous alloy sample is obtained by a carbon-sulfur analyzer.
[0018] Furthermore, in S3, the volume V of the alloy sample is determined based on the weight and density of the alloy sample, and the contact area S between the alloy sample and the inner surface of the high-purity graphite crucible is determined based on the shape and size of the inner surface of the high-purity graphite crucible.
[0019] Further, the maximum C solubility Cs in S4 is obtained by the following steps:
[0020] S41, arc melting an alloy sample having the same metal composition and ratio as in S1 to obtain a button ingot sample;
[0021] S42, remelting the button ingot sample obtained in S41 in a vacuum arc furnace, and suction casting it into a high-purity copper mold by suction casting, cooling and shaping it, and obtaining N solubility measurement samples with the same volume after machining;
[0022] S43, preparing N glass tubes and 2N high-purity carbon blocks, dividing the 2N high-purity carbon blocks into N groups, each group of high-purity carbon blocks corresponding to a solubility measurement sample and a glass tube, and sequentially placing one high-purity carbon block, the solubility measurement sample and another high-purity carbon block in each group into corresponding glass tubes;
[0023] S44, evacuating the glass tube filled with the high-purity carbon block and the solubility measurement sample, and then filling the interior of the glass tube with high-purity argon gas and sealing the tube;
[0024] S45, dividing the N glass tubes in S44 into M groups, placing the M groups of glass tubes in a muffle furnace respectively, and heating and keeping them warm at different heating temperatures, wherein the glass tubes in each group have different keeping times, so that the solubility measurement sample and the high-purity graphite block produce different degrees of interface reaction, wherein the heating temperature of each group of glass tubes corresponds to the melting temperature of each group of alloy samples in S1;
[0025] S46, when each glass tube reaches the insulation time, the glass tube is taken out from the muffle furnace, the glass tube is broken and the solubility measurement sample containing the dissolved C element is taken out, and the carbon content of the solubility measurement sample is measured by a carbon-sulfur analyzer. After measuring the carbon content of all solubility measurement samples, the C solubility Cs with the maximum interfacial reaction at different melting temperatures can be obtained.
[0026] Furthermore, the pressure of the high-purity argon gas in S44 is 0.4-0.6 MPa.
[0027] Furthermore, the glass tube in S45 is placed vertically into the muffle furnace to ensure that the high-purity carbon block is in full contact with the solubility measurement sample.
[0028] Furthermore, the insulation time of each glass tube in each group of glass tubes in S44 increases according to a geometric progression with a common ratio of 2, and the initial insulation temperature is 0.5h.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] 1. The present invention uses a high-purity graphite crucible equipped with medium-frequency induction melting technology to prepare amorphous alloys. During the melting process, the small atoms C in the high-purity graphite crucible can be forced to diffuse into the gaps between the atoms of the amorphous alloy to form a solid solution, thereby increasing the free volume of the shear band and increasing the degree of amorphousness. At the same time, based on the above method, the C increment of the amorphous alloy at a certain melting temperature and any melting time when the high-purity graphite crucible is used to melt the amorphous alloy can be determined, so that the desired amorphous alloy sample can be prepared.
[0031] 2. The method of improving the strength and plasticity of amorphous alloys of the present invention has stable technology, low cost, and low energy consumption, and can effectively improve the strength and plasticity of amorphous alloys.
[0032] 3. The method of improving the strength and plasticity of amorphous alloys of the present invention is also applicable to alloys with different compositions and metal ratios, and is also applicable to the diffusion of different elements. For example, a quartz crucible is used to melt an amorphous alloy to force the O element to diffuse into the gaps in the amorphous alloy, thereby strengthening the amorphous alloy by solid solution or forming a crystal phase. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] The accompanying drawings are considered as a part of this application and are used to provide a further understanding of the present invention.
[0034] Figure 1 This is a schematic diagram of the state when the glass tube containing the high-purity carbon block and the solubility measurement sample is sealed.
[0035] Figure 2 Schematic diagram of the structure of the high-purity graphite crucible in Example 1.
[0036] Figure 3 is the temperature at different melting points in Example 1 The coordinate system with t.
[0037] Figure 4 This is a schematic diagram of the compressive strength and plasticity results of each amorphous alloy sample after uniaxial compression tests on amorphous alloy samples at different melting temperatures and melting times.
[0038] Figure 5 This is a schematic diagram of the shear band volume results of each amorphous alloy sample after nanoindentation tests on amorphous alloy samples at different melting temperatures and melting times.
[0039] Explanation of reference numerals: 1 - solubility measurement sample; 2 - high purity carbon block; 3 - glass tube. DETAILED DESCRIPTION
[0040] The present invention is described in detail below in conjunction with specific embodiments.
[0041] This embodiment provides a method for improving the strength and plasticity of an amorphous alloy, and the improvement process is shown in the following steps:
[0042] S1, weighing various metal raw materials according to the target atomic percentage, the metal raw materials are all high-purity raw materials, uniformly mixing the various metal raw materials and obtaining alloy samples, dividing the alloy samples into multiple portions, and the multiple alloy samples are further divided into M groups, wherein M is an integer ≥3, that is, at least 3 test groups are formed; the M groups of alloy samples are respectively placed in a medium frequency induction furnace equipped with a high-purity graphite crucible, and before induction melting of each alloy sample, the high-purity graphite crucible is first evacuated and filled with 0.4MPa-0.6MPa of high-purity argon gas to avoid oxidation reaction of the alloy sample during the melting process; at the beginning of melting, different alloy samples are set Melting temperature, that is, M groups of alloy samples correspond to M kinds of melting temperatures, different melting times are set for different alloy samples in each group, and the time when the alloy sample is cleared is recorded as the timing zero point, so that the influence of melting temperature and melting time on the diffusion amount of small atomic C in the high-purity graphite crucible can be determined; in the process of melting the alloy in the high-purity graphite crucible, the small atomic C can be forced to diffuse and dissolve into the gaps composed of the amorphous alloy atoms, thereby increasing the free volume of the shear band and the degree of amorphousness; after each alloy sample is melted, the molten alloy is poured into a high-purity copper mold for cooling, and a plurality of amorphous alloy samples diffused with the C element are obtained in sequence;
[0043] S2, after all alloy samples are melted and cooled, the C content C(t) of each amorphous alloy sample in S1 is obtained by a carbon-sulfur analyzer;
[0044] S3, based on the weight and density of any alloy sample, determine the volume V of the alloy sample, and based on the shape and size of the inner surface of the high-purity graphite crucible, determine the contact area S between the alloy sample and the inner surface of the high-purity graphite crucible. Since the volume and weight of each alloy sample are the same, only the volume V of one alloy sample and the contact area S between the alloy sample and the inner surface of the high-purity graphite crucible need to be measured;
[0045] S4, directly using the method of diffusing small-sized C atoms into the amorphous alloy to obtain the maximum C solubility Cs of the interface reaction of the alloy sample with the same metal composition and proportion as in S1 at the above M different melting temperatures, and obtaining the relationship between the C solubility, melting time and melting temperature in the alloy sample through the maximum C solubility Cs. The steps for obtaining the maximum C solubility Cs are as follows:
[0046] S41, weighing various metal raw materials with the same metal composition and proportion as in S1, the metal raw materials are also high-purity raw materials, uniformly mixing the various metal raw materials to obtain alloy sample 2, and arc melting the alloy sample 2 to obtain a high-purity button ingot sample;
[0047] S42, remelting the high-purity button ingot sample obtained in S41 in a vacuum arc furnace, and suction casting it into a rectangular high-purity copper mold by suction casting, cooling and shaping, and obtaining N solubility measurement samples 1 with the same volume after machining;
[0048] S43, prepare N glass tubes 3 and 2N high-purity carbon blocks 2, divide the 2N high-purity carbon blocks 2 into N groups, each group of high-purity carbon blocks 2 corresponds to a solubility measurement sample 1 and a glass tube 3, and sequentially place one high-purity carbon block 2, the solubility measurement sample 1 and another high-purity carbon block 2 in each group into the corresponding glass tube 3, wherein the high-purity carbon block 2 directly provides small-sized C atoms for the solubility measurement sample 1;
[0049] S44, evacuating the glass tube 3 filled with the high-purity carbon block 2 and the solubility measurement sample 1, and then filling the glass tube 3 with 0.4Mpa to 0.6Mpa high-purity argon gas, and then using acetylene to heat the tube mouth of the glass tube 3 to achieve tube sealing, so as to avoid oxidation reaction between the solubility measurement sample 1 and the high-purity carbon block 2 during the interface reaction process;
[0050] S45, divide the N glass tubes 3 containing the high-purity carbon block 2 and the solubility measurement sample 1 into M groups, and prepare M muffle furnaces, each group of glass tubes 3 corresponds to one muffle furnace, and vertically place the glass tubes 3 in each group into the corresponding muffle furnace to ensure that the solubility measurement sample 1 in the glass tube 3 can fully contact with the high-purity carbon block 2 on the upper and lower sides; set a heating temperature for each group of muffle furnaces, and the heating temperatures of the M groups of glass tubes 3 in this step correspond to and are the same as the melting temperatures of the M groups of alloy samples in S1, that is, in this embodiment, at least 3 groups of maximum C solubility Cs values at different melting temperatures are obtained, each The maximum C solubility Cs corresponds to a test group in S1; in addition, each group of glass tubes 3 needs to be kept warm in addition to being heated at the corresponding heating temperature, and the holding time of each glass tube 3 in each group of glass tubes 3 increases in a geometric progression with a common ratio of 2, and the initial holding temperature is 0.5h, that is, the holding time of the first glass tube 3 in each group is 0.5h, the holding time of the second glass tube 3 is 1h, the holding time of the third glass tube 3 is 2h, the holding time of the fourth glass tube 3 is 4h..., and the holding is carried out according to such a rule so that the solubility measurement sample 1 and the high-purity carbon block 2 produce different degrees of interface reaction;
[0051] S46, when each glass tube 3 reaches the insulation time, the glass tube 3 is taken out from the muffle furnace, the glass tube 3 is broken and the solubility measurement sample 1 dissolved with C is taken out, and the carbon content of the solubility measurement sample 1 is measured by a carbon-sulfur analyzer. After measuring the carbon content of all the solubility measurement samples 1, the C solubility Cs with the maximum interface reaction under different heating temperatures can be obtained;
[0052] S5, based on the C content C(t) and the maximum C solubility Cs of each amorphous alloy sample, the rate constant k at different melting temperatures is obtained:
[0053]
[0054] Wherein, Co is the initial C solubility of the alloy sample (which can be regarded as 0), and t is the smelting time;
[0055] S6. Based on the rate constant k obtained in S5, the C increment of the alloy sample melted in a high-purity graphite crucible at any time can be obtained.
[0056] This embodiment uses a high-purity graphite crucible equipped with medium-frequency induction melting technology to prepare an amorphous alloy. During the melting process, the small atomic C in the high-purity graphite crucible can be forced to diffuse into the gaps between the atomic components of the amorphous alloy, thereby increasing the free volume of the shear band and increasing the degree of amorphism. At the same time, this embodiment uses at least three test groups to prove that based on the above-mentioned method for improving the strength and plasticity of amorphous alloys, the C increment of the amorphous alloy at a certain melting temperature and any melting time when the high-purity graphite crucible is melting an amorphous alloy can be determined, so that the required amorphous alloy samples with different degrees of small atomic C increments can be prepared. The method for improving the strength and plasticity of amorphous alloys in this embodiment is simple and can be achieved only by using a high-purity graphite crucible equipped with medium-frequency induction melting technology. The overall technology is stable, low-cost, and low-energy consumption, and can effectively improve the strength and plasticity of amorphous alloys. In addition, the method of improving the strength and plasticity of amorphous alloys in this embodiment is also applicable to alloys with different compositions and metal ratios, and is also applicable to the diffusion of different elements. For example, a quartz crucible is used to melt an amorphous alloy to force the O element to diffuse into the gaps in the amorphous alloy to strengthen the amorphous alloy through solid solution strengthening or forming a crystal phase.
[0057] Embodiment 1:
[0058] S1, weighing various metal raw materials according to the target atomic percentage of Zr 52.5%, Cu 17.9%, Ni 14.6%, Al 10%, Ti 5%, and each metal raw material is a high-purity raw material. The metal raw materials are uniformly mixed to obtain an alloy sample, and 50g of the alloy sample is weighed, and a total of 9 portions are weighed. The 9 portions of alloy samples are equally divided into 3 test groups, and the 3 groups of alloy samples are respectively placed in a medium frequency induction furnace equipped with a high-purity graphite crucible. Before induction melting of each alloy sample, the high-purity graphite crucible is first evacuated and filled with 0.5MPa of high-purity argon gas to avoid oxidation reaction of the alloy sample during the melting process;
[0059] At the beginning of smelting, three melting temperatures were set for the three test groups, namely 1150K, 1250K and 1350K. One test group was melted at 1150K, and the three alloy samples in this group were melted at 5min, 25min and 45min respectively. One test group was melted at 1250K, and the three alloy samples in this group were melted at 5min, 25min and 45min respectively. The other test group was melted at 1350K, and the three alloy samples in this group were also melted at 5min The alloy was melted at 1150K, 1250K and 1350K and at 5min, 25min and 45min, so that the diffusion amount of small atomic C in the amorphous alloy obtained at the melting temperatures of 5min, 25min and 45min can be determined, wherein the melting time of the alloy sample is recorded as the timing zero point when the alloy sample is cleared; in the process of melting the alloy in a high-purity graphite crucible, the small atomic C can be forced to diffuse and dissolve into the gaps of the amorphous alloy, thereby increasing the free volume of the shear band and improving the degree of amorphousness;
[0060] After each alloy sample is melted, the molten alloy is poured into a high-purity copper mold and cooled to obtain an amorphous alloy sample diffused with the C element. After all alloy samples are melted and cooled, a total of 9 amorphous alloy samples diffused with the C element are obtained;
[0061] S2, the C content C(t) of 9 amorphous alloy samples is obtained by a carbon-sulfur analyzer. The C content C(t) of each amorphous alloy sample is shown in Table 1:
[0062] Table 1: Carbon content of amorphous alloy samples prepared at three melting temperatures and melting times using high purity graphite crucible equipped with medium frequency induction melting technology
[0063]
[0064] It can be seen from Table 1 that with the increase of melting temperature and melting time, the C content C(t) of the amorphous alloy sample also gradually increases.
[0065] S3, since the weight of each alloy sample is 50g, the alloy sample melts when 50g of the alloy sample is placed in the crucible for smelting, and the density of each metal is determined, so the volume V of each alloy sample can be calculated based on the weight and density of the alloy sample, V = 7.58e-6m 3 The contact area S between the alloy sample and the inner surface of the high-purity graphite crucible is determined based on the shape and size of the inner surface of the high-purity graphite crucible. The high-purity graphite crucible of this embodiment adopts a truncated cone-shaped crucible cavity, such as Figure 2As shown in the figure, the inner diameter of the crucible bottom is 21 mm, the inner diameter of the crucible mouth is 25 mm, and the height of the crucible cavity is 45 mm. Based on the volume V of the alloy sample, the contact area S between the alloy sample and the inner surface of the high-purity graphite crucible is calculated to be 1.73e-3m 2 .
[0066] S4, directly diffuses small-sized C atoms into the amorphous alloy to obtain the maximum C solubility Cs of the interface reaction at the three different melting temperatures of 1150K, 1250K and 1350K for the alloy sample with the same metal composition and proportion as in S1. The relationship between the C solubility, melting time and melting temperature in the alloy sample is obtained through the maximum C solubility Cs. The steps for obtaining the maximum C solubility Cs are as follows:
[0067] S41, weighing various metal raw materials according to the target atomic percentage of Zr 52.5%, Cu 17.9%, Ni 14.6%, Al 10%, and Ti 5%, uniformly mixing and obtaining alloy sample 2, and arc melting the alloy sample 2 to obtain a button ingot sample;
[0068] S42, remelting the button ingot sample obtained in S41 in a vacuum arc furnace, and suction casting it into a rectangular high-purity copper mold with a width and a height of 3 mm by suction casting, cooling and shaping it, taking out the shaped sample from the high-purity copper mold, cutting the shaped sample with a slow diamond saw, and obtaining 27 solubility measurement samples 1 with a length, a width and a height of 3 mm;
[0069] S43, prepare 27 glass tubes 3 with an inner diameter of 6 mm and 54 high-purity carbon blocks 2 with a diameter of 5.9 mm and a height of 3 mm, divide the 54 high-purity carbon blocks 2 into 27 groups, each group of high-purity carbon blocks 2 corresponds to a solubility measurement sample 1 and a glass tube 3, and sequentially place one high-purity carbon block 2, the solubility measurement sample 1 and another high-purity carbon block 2 in each group into the corresponding glass tube 3, wherein the high-purity carbon block 2 directly provides small-sized C atoms for the solubility measurement sample 1;
[0070] S44, evacuate the glass tube 3 filled with the high-purity carbon block 2 and the solubility measurement sample 1, then fill the interior with 0.5 MPa high-purity argon gas, and then use acetylene to heat the glass tube 3 to seal the tube, so as to avoid oxidation reaction between the solubility measurement sample 1 and the high-purity carbon block 2 during the interface reaction;
[0071] S45, 27 glass tubes 3 containing high-purity carbon blocks 2 and solubility measurement samples 1 are equally divided into 3 groups, and 3 muffle furnaces are prepared, each group of glass tubes 3 corresponds to one muffle furnace, and the glass tubes 3 in each group are vertically placed into the corresponding muffle furnace to ensure that the solubility measurement samples 1 in the glass tubes 3 can fully contact with the high-purity carbon blocks 2 on the upper and lower sides; one group of muffle furnaces heats the glass tubes 3 at a temperature of 1150K, and the heating time of the 9 glass tubes 3 in the group is 0.5h, 1h, 2h, 4h, 8h, 16h, 32h, 64h, and 128h respectively; One group of muffle furnaces heats the glass tubes 3 at a temperature of 1250K, and the heating times of the 9 glass tubes 3 in the group are respectively 0.5h, 1h, 2h, 4h, 8h, 16h, 32h, 64h, and 128h; another group of muffle furnaces heats the glass tubes 3 at a temperature of 1350K, and the heating times of the 9 glass tubes 3 in the group are respectively 0.5h, 1h, 2h, 4h, 8h, 16h, 32h, 64h, and 128h, so that the solubility measurement sample 1 and the high-purity carbon block 2 produce different degrees of interface reaction at different heating temperatures and heating times;
[0072] S46, when each glass tube 3 reaches the insulation time, the glass tube 3 is taken out from the muffle furnace, the glass tube 3 is broken and the solubility measurement sample 1 dissolved with C is taken out, and the carbon content of the solubility measurement sample 1 is measured by a carbon-sulfur analyzer. After measuring the carbon content of all solubility measurement samples 1, the maximum C solubility Cs of the interface reaction at three heating temperatures of 1150K, 1250K and 1350K can be obtained, wherein the maximum C solubility Cs at the heating temperature of 1150K is 1.24wt.%, the maximum C solubility Cs at the heating temperature of 1250K is 1.83wt.%, and the maximum C solubility Cs at the heating temperature of 1350K is 2.78wt.%;
[0073] S5, using the maximum C solubility Cs at a heating temperature of 1150K obtained in step S46, and C(t) at a melting temperature of 1150K and a melting time of 5min, 25min and 45min obtained in step S2, and based on the kinetic formula Calculate the melting time of 5min, 25min and 45min respectively. Establish and t coordinate system, the above three melting times Substitution Figure 4 In the coordinate system of , the melting temperature of 1150K is obtained. The value of is used to obtain the rate constant k at a melting temperature of 1150K; the same calculation method is used to obtain the rate constant k at melting temperatures of 1250K and 1350K, respectively, and then the C increment C(t) of the alloy sample melted in a high-purity graphite crucible at any time can be obtained.
[0074] Uniaxial compression test and nanoindentation test were carried out on amorphous alloy samples prepared by high-purity graphite crucible equipped with medium-frequency induction melting technology to verify whether in-situ diffusion of C element by high-purity graphite crucible can effectively improve the strength and plasticity of amorphous alloy and obtain the optimal C content. The specific verification process is as follows:
[0075] Uniaxial compression test: 5 amorphous alloy samples in S1 were selected as specimens for uniaxial compression test. The 5 specimens were machined to obtain compression specimens with a diameter of 4 mm and a height of 6 mm. The 5 compression specimens were set as specimen 1 (1150K, 25 min), specimen 2 (1250K, 25 min), specimen 3 (1350K, 5 min), specimen 4 (1350K, 25 min) and specimen 5 (1350K, 45 min), respectively. The 5 compression specimens were axially compressed by a universal compressor, and the compression rate was 0.01s -1 Finally, the compressive strength and plasticity of the five compression specimens were obtained. The test results are shown in Figure 4 As shown in the figure, the pink curve value represents the plasticity of the 5 compression specimens, and the purple curve value represents the compressive strength of the 5 compression specimens. It can be seen from the figure that specimen 4 (1350K, 25min) has the strongest compressive strength and plasticity and the best mechanical properties, which proves that the in-situ diffusion of C element in high-purity graphite crucible can effectively improve the strength and plasticity of amorphous alloys.
[0076] Nanoindentation test: Select 5 amorphous alloy samples in S1 as specimens for nanoindentation test. Machine the 5 specimens to obtain indentation specimens with a diameter of 4 mm and a height of 3 mm. The 5 indentation specimens are set as specimen 1 (1150K, 25 min), specimen 2 (1250K, 25 min), specimen 3 (1350K, 5 min), specimen 4 (1350K, 25 min) and specimen 5 (1350K, 45 min). Polish the 5 indentation specimens before the test. Then randomly select 4 4×4 dot arrays on each indentation specimen. The distance between each point is 10 um. That is to say, each indentation specimen has 64 pressure points. Use a Berkovich diamond indenter with a tip diameter of 10 nm to pressurize the pressure points of each indentation specimen. The loading rate is 1 mN / s, the maximum load is 15 mN, and the recording frequency is 300 Hz. Then, by
[0077]
[0078] Where: f is the cumulative distribution function of the first yield in the nanoindentation experiment, kT is the thermal energy, dτ / dt is the loading rate of the nanoindentation test, τ is the maximum shear force at the first yield in the nanoindentation experiment, and V* is the calculated shear band free volume of the amorphous alloy. Therefore, by converting ln[ln(1-f) -1 ] as the ordinate and τ as the abscissa, the slope can be obtained by linear fitting the coordinate points. The shear band free volume V* can be obtained.
[0079] According to the above method, V* / kT of the five indentation specimens are calculated respectively. The specific calculation results are shown in Table 2:
[0080] Table 2: V* / kT values of the five indentation specimens obtained
[0081]
[0082]
[0083] Combining Table 1 and Figure 5 It can be seen that the free volume of the shear band of the indentation specimen varies with the carbon content C(t), and the free volume of the shear band of specimen 4 (1350K, 25min) is the largest.
[0084] Through the above two tests, it can be proved that the shear band free volume of specimen 4 (1350K, 25min) is the largest, and has the greatest compressive strength and plasticity, proving that the introduction of carbon atoms improves the amorphous degree of strong plasticity and increases the shear band free volume, and the most suitable carbon content for this alloy composition is 1170ppm. After obtaining the optimal carbon content, the required holding time at a temperature suitable for production conditions can be obtained according to the formula in step S5.
[0085] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for improving the strength and plasticity of an amorphous alloy, characterized in that: The improvement process is as follows: S1, weighing each metal raw material according to the target atomic percentage, uniformly mixing and obtaining an alloy sample, dividing the alloy sample into multiple portions, and the multiple alloy samples are further divided into M groups, and the M groups of alloy samples are respectively placed in a medium frequency induction furnace equipped with a high-purity graphite crucible, and before induction melting of each alloy sample, the high-purity graphite crucible is first evacuated and filled with high-purity argon gas; at the beginning of melting, a different melting temperature is set for each group of alloy samples, and different melting times are set for different alloy samples in each group, and the time when the alloy sample is cleared is recorded as the timing zero point; after the melting of each alloy sample is completed, the molten alloys at different melting temperatures and melting times are respectively poured into a cooling mold for cooling, and a plurality of amorphous alloy samples diffused with C elements are obtained in sequence; S2, obtaining the C content C(t) of each amorphous alloy sample in S1; S3, determine the volume V of any alloy sample in S1, and deduce the contact area S between the alloy sample and the inner surface of the high-purity graphite crucible; S4, obtaining the maximum C solubility Cs of the interface reaction of the alloy sample at the above different melting temperatures; S5, based on the C content C(t) and the maximum C solubility Cs of each amorphous alloy sample, the rate constant k at different melting temperatures is obtained: Where Co is the initial C solubility of the alloy sample, and t is the melting time; S6. Based on the rate constant k obtained in S5, the C increment of the alloy sample melted in a high-purity graphite crucible at any time can be obtained.
2. A method for improving the strength and plasticity of an amorphous alloy according to claim 1, characterized in that: The pressure of the high-purity argon gas filled in the high-purity graphite crucible in S1 is 0.4 MPa to 0.6 MPa.
3. A method for improving the strength and plasticity of an amorphous alloy according to claim 1, characterized in that: The high-purity graphite crucible in S1 is provided with a boron nitride ceramic sleeve on the outside to protect the sensor.
4. A method for improving the strength and plasticity of an amorphous alloy according to claim 1, characterized in that: The cooling mold in S1 is a high-purity copper mold.
5. The method for improving the strength and plasticity of an amorphous alloy according to claim 1, characterized in that: S2 is the C content C(t) of each amorphous alloy sample obtained by a carbon-sulfur analyzer.
6. A method for improving the strength and plasticity of an amorphous alloy according to claim 1, characterized in that: In S3, the volume V of the alloy sample is determined based on the weight and density of the alloy sample, and the contact area S between the alloy sample and the inner surface of the high-purity graphite crucible is determined based on the shape and size of the inner surface of the high-purity graphite crucible.
7. A method for improving the strength and plasticity of an amorphous alloy according to claim 1, characterized in that: The maximum C solubility Cs in S4 is obtained by the following steps: S41, arc melting an alloy sample having the same metal composition and ratio as in S1 to obtain a button ingot sample; S42, remelting the button ingot sample obtained in S41 in a vacuum arc furnace, and suction casting it into a high-purity copper mold by suction casting, cooling and shaping it, and obtaining N solubility measurement samples with the same volume after machining; S43, preparing N glass tubes and 2N high-purity carbon blocks, dividing the 2N high-purity carbon blocks into N groups, each group of high-purity carbon blocks corresponding to a solubility measurement sample and a glass tube, and sequentially placing one high-purity carbon block, the solubility measurement sample and another high-purity carbon block in each group into corresponding glass tubes; S44, evacuating the glass tube filled with the high-purity carbon block and the solubility measurement sample, and then filling the interior of the glass tube with high-purity argon gas and sealing the tube; S45, dividing the N glass tubes in S44 into M groups, placing the M groups of glass tubes in a muffle furnace respectively, and heating and keeping them warm at different heating temperatures, wherein the glass tubes in each group have different keeping times, so that the solubility measurement sample and the high-purity graphite block produce different degrees of interface reaction, wherein the heating temperature of each group of glass tubes corresponds to the melting temperature of each group of alloy samples in S1; S46, when each glass tube reaches the insulation time, the glass tube is taken out from the muffle furnace, the glass tube is broken and the solubility measurement sample containing the dissolved C element is taken out, and the carbon content of the solubility measurement sample is measured by a carbon-sulfur analyzer. After measuring the carbon content of all solubility measurement samples, the C solubility Cs with the maximum interfacial reaction at different melting temperatures can be obtained.
8. A method for improving the strength and plasticity of an amorphous alloy according to claim 6, characterized in that: The pressure of the high-purity argon gas in S44 is 0.4-0.6 MPa.
9. A method for improving the strength and plasticity of an amorphous alloy according to claim 6, characterized in that: The glass tube in S45 is placed vertically in the muffle furnace to ensure that the high-purity carbon block and the solubility measurement sample can fully contact each other.
10. A method for improving the strength and plasticity of an amorphous alloy according to claim 6, characterized in that: The insulation time of each glass tube in each group of glass tubes in S44 increases according to a geometric progression with a common ratio of 2, and the initial insulation temperature is 0.5h.
Citation Information
Patent Citations
Alloying method for high-strength anti-seismic steel bar
CN113802044A
Zr-Co-Al-Mo amorphous alloy with high plasticity at room temperature and preparation method of Zr-Co-Al-Mo amorphous alloy
CN117737617A
Method for improving room-temperature plasticity of amorphous alloy
CN118726877A
NiCrMo STEEL AND METHOD FOR PRODUCING THE SAME
JP2021134388A
Nickel-based deformed high-temperature alloy having high aluminum content and preparation method therefor
WO2021174726A1